A Free‐Standing and Self‐Healable 2D Supramolecular Material Based on Hydrogen Bonding: A Nanowire Array with Sub‐2‐nm Resolution. Issue 21 (7th April 2017) - Li, Ming; Song, Mengyao; Wu, Guitai; Tang, Zhenyu; Sun, Yunfeng; He, Yunbin; Li, Jinhua; Li, Lei; Gu, Haoshuang; Liu, Xiong; Ma, Chuang; Peng, Zefei; et al.
Abstract : In many 2D materials reported thus far, the forces confining atoms in a 2D plane are often strong interactions, such as covalent bonding. Herein, the first demonstration that hydrogen (H)‐bonding can be utilized to assemble polydiacetylene (a conductive polymer) toward a 2D material, which is stable enough to be free‐standing, is shown. The 2D material is well characterized by a large number of techniques (mainly different microscopy techniques). The H‐bonding allows splitting of the material into ribbons, which can reassemble, similar to a zipper, leading to the first example of a healable 2D material. Moreover, such technology can easily create 2D, organic, conductive nanowire arrays with sub‐2‐nm resolution. This material may have potential applications in stretchable electronics and nanowire cross‐bar arrays. Abstract : Hydrogen (H)‐bonding can be utilized to construct a free‐standing 2D material . The H‐bonding allows splitting of the material into ribbons, which can re‐assemble (self‐heal), similar to a zipper. Such a strategy can easily create 2D, organic, conductive nanowire arrays with sub‐2‐nm resolution. This material may have applications in stretchable electronics and cross‐bar arrays.